2015
DOI: 10.1039/c5ob01062d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of galacto-noeurostegine and its 2-deoxy analogue as glycosidase inhibitors

Abstract: An epimer of the known glycosidase inhibitor noeurostegine, galacto-noeurostegine, was synthesised in 21 steps from levoglucosan and found to be a potent, competitive and highly selective galactosidase inhibitor of Aspergillus oryzae β-galactosidase. Galacto-noeurostegine was not found to be an inhibitor of green coffee bean α-galactosidase, yeast α-glucosidase and E. coli β-galactosidase, whereas potent but non-competitive inhibition against sweet almond β-glucosidase was established. The 2-deoxy-galacto-noeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…2). Since galacto-noeurostegine (4-epi-noeurostegine) is not an inihibitor of green coffee beans α-galactosidase, but calystegine and noeurostegine inhibit this enzyme potently, we have previously speculated that the two former azasugars would bind in a nojirimycin (NJ) binding mode 24 placing the ethylene bridge in the same position as nojiristegine (1). The observation, that nojiristegine is not an inhibitor of this enzyme, brings our previous suggestion into question.…”
Section: Inhibition Studiesmentioning
confidence: 97%
See 3 more Smart Citations
“…2). Since galacto-noeurostegine (4-epi-noeurostegine) is not an inihibitor of green coffee beans α-galactosidase, but calystegine and noeurostegine inhibit this enzyme potently, we have previously speculated that the two former azasugars would bind in a nojirimycin (NJ) binding mode 24 placing the ethylene bridge in the same position as nojiristegine (1). The observation, that nojiristegine is not an inhibitor of this enzyme, brings our previous suggestion into question.…”
Section: Inhibition Studiesmentioning
confidence: 97%
“…31 Interestingly, the indium mediated Barbier allylation was previously found to be dependent on the C-β stereochemistry in the synthesis of noeurostegine and galacto-noeurostegine (entries 4 and 5), where the aldehyde is flanked by a benzyloxy group (Table 1). 22,24 For these examples, the aldehyde leading to noeurostegine (entry 4) having the same stereochemistry as 7, the S-product dominated, while the opposite was true for the aldehyde leading to galacto-noeurostegine (entry 5).…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%
See 2 more Smart Citations
“…Direct iodination of the primary alcohol followed by zinc mediated fragmentation afforded the corresponding aldehyde which was transformed in 11 steps to noeurostegine (Scheme 29b). In 2015, the same authors reported the synthesis of its epimer, galacto‐noeurostegine, using a related synthetic strategy [86b] …”
Section: Miscellaneous Nucleophilesmentioning
confidence: 99%